Synergistic effect of synthetic derivatives of 1,3,4-thiadiazole with amphotericin B in antifungal therapy - Dominika Kubera; Adrianna Sławińska-Brych; Agnieszka Dróźdż; Alina Olender; Agnieszka Bogut; Arkadiusz Matwijczuk; Dariusz Karcz; Magdalena Kimsa-Dudek; Joanna Magdalena Gola; Celina Kruszniewska-Rajs; Jolanta Adamska; Magdalena Szukała; et al. (Scientific Reports)
Abstract Amphotericin B (AmB) is a potent antifungal agent with minimal resistance among clinical isolates, but its use is limited by severe side effects. Reducing its toxicity through combination therapy with synergistic compounds is a promising strategy. This study investigates the antifungal potential of 1,3,4-thiadiazole derivatives, focusing on AT2 and AT10, against Candida species. AT2 demonstrated the highest activity, achieving complete inhibition at 128 µg/mL and notable suppression at lower concentrations. The combination of AT2 and AT10 with amphotericin B exhibited synergistic effects, leading to significant structural alterations in the fungal cell wall, including reduced β-glucan levels and increased synthesis of mannan and phosphomannan. These modifications correlated with enhanced antifungal efficacy without exacerbating cytotoxicity toward human fibroblasts and renal epithelial cells. The spectroscopic analysis suggested that the synergy arose from both cell wall disruptions and amphotericin B disaggregation. These findings highlight the potential of thiadiazole-based combination therapies for combating resistant fungal infections.